Diagnostic Accuracy of Non-Contrast CT Scanning in Fungal Sinusitis, Taking Fungal Culture as Gold Standard - Siddique, Ayesha; Pasha, Nazahat (Biological and Clinical Sciences Research Journal, 2025)
Fungal sinusitis represents a significant diagnostic and therapeutic challenge, especially in immunocompromised patients. Timely and accurate Diagnosis is essential to reduce morbidity and mortality. While fungal culture remains the Gold standard, it is invasive and time-consuming. Non-contrast computed tomography (CT) provides a rapid and non-invasive alternative. Still, its diagnostic accuracy requires further evaluation in the Pakistani population, where risk factors such as uncontrolled diabetes and environmental exposure are common. Objective: To determine the diagnostic accuracy of non-contrast CT scanning in detecting fungal sinusitis, using fungal culture as the Gold standard. Methods: This cross-sectional study was conducted over six months from July 2023 to December 2023 at the Department of Diagnostic Radiology, Chaudhry Pervaiz Elahi Institute of Cardiology (CPEIC), Multan. A total of 121 patients aged 18–60 years, presenting with clinical features of suspected fungal sinusitis, were enrolled through non-probability consecutive sampling. Baseline demographic data, diabetes status, and history of steroid inhaler use were recorded. All patients underwent non-contrast CT scanning of the paranasal sinuses using standardized parameters and interpretation by a senior radiologist. Functional endoscopic sinus surgery (FESS) was performed in all cases, and biopsy specimens were sent for fungal culture, which served as the reference standard for Diagnosis. Data was analyzed using SPSS version 23.0 to calculate sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy. Results: The mean age of the patients was 39.8 ± 11.2 years, with the majority in the 31–40-year age group. Males comprised 56.2% of the cohort, and 40.5% had diabetes mellitus. A non-contrast CT scan identified fungal sinusitis in 92 (76.0%) patients, while fungal culture results were positive in 88 (72.7%) patients. When compared to fungal culture, CT scanning demonstrated a sensitivity of 96.59%, specificity of 79.41%, PPV of 92.39%, NPV of 90.00%, and an overall diagnostic accuracy of 92.56%. Conclusion: Non-contrast CT scanning shows excellent sensitivity and reasonable specificity for diagnosing fungal sinusitis, supporting its role as a first-line diagnostic tool in the Pakistani population. Its rapid availability and non-invasive nature make it an effective modality to guide timely intervention, particularly in high-risk groups such as diabetic patients.